Selvamicin, an atypical antifungal polyene from two alternative genomic contexts - Van Arnam, Ethan B. (2016)
The bacteria harbored by fungus-growing ants produce a variety of small molecules that help maintain a complex multilateral symbiosis. In a survey of antifungal compounds from these bacteria, we discovered selvamicin, an unusual antifungal polyene macrolide, in bacterial isolates from two neighboring ant nests. Selvamicin resembles the clinically important antifungals nystatin A1 and amphotericin B, but it has several distinctive structural features: a noncationic 6-deoxymannose sugar at the canonical glycosylation site and a second sugar, an unusual 4-O-methyldigitoxose, at the opposite end of selvamicin’s shortened polyene macrolide. It also lacks some of the pharmacokinetic liabilities of the clinical agents and appears to have a different target. Whole genome sequencing revealed the putative type I polyketide gene cluster responsible for selvamicin’s biosynthesis including a subcluster of genes consistent with selvamicin’s 4-O-methyldigitoxose sugar. Although the selvamicin biosynthetic cluster is virtually identical in both bacterial producers, in one it is on the chromosome, in the other it is on a plasmid. These alternative genomic contexts illustrate the biosynthetic gene cluster mobility that underlies the diversity and distribution of chemical defenses by the specialized bacteria in this multilateral symbiosis.